Gender-Related Impact of Forest and Peatland Fires on Air Quality and Lung Function Analysis - Tumpal Simatupang; Yetrie Ludang; Nawan; Bambang S. Lautt; Liswara Neneng (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
he issue of air quality continues to be a major concern for both the environment and human health on a global scale, especially in developing nations. In 2015, Indonesia garnered international recognition as a result of the extensive forest and land fires. Exposure to PM particles in the air presents a substantial health hazard to individuals participating in their everyday routines. Research on the effects of forest fires on respiratory health in Central Kalimantan is still lacking. The Chest Miyagi multipurpose HI-801 spirometer, which was calibrated, was used to do lung function measurements. The participants were assessed while standing indoors in an environment with consistent air movement. Prior to the test, the individual's height and weight were measured and recorded in the spirometer, which then used this data to automatically determine the expected lung function. A sample size of 215 respondents who fulfilled the research criteria was selected for the study. The examinations took place in 7 urban and rural locations that were considered to be most susceptible to forest and land fires, based on the researcher's subjective judgment. These locations were chosen to meet the required sample size and were in close proximity to the fire sources. The spirometry device measures lung function, including forced vital capacity (FVC), forced expiratory volume in one second (FEV1), the ratio of FEV1 to FVC, and Forced Expiratory Flow (FEF). This study aimed to assess the effect of recurrent forest fires on lung function, specifically in relation to gender, in Palangka Raya City, Pulang Pisau Regency, and Kapuas Regency, located in the Central Kalimantan Province. The analysis was conducted using spirometry tests. There were no notable disparities in lung function among the respondents based on their gender.